The master's tools: Media repurposing of exclusionary metaphors to challenge racist constructions of migrants. (January 2022) - Martin, Catherine Ann; Fozdar, Farida
Metaphors are powerful mechanisms by which to rally exclusionary nationalist sentiment without necessarily appearing racist. However, sometimes those metaphors are challenged, inverting exclusionary functions. In this paper, we track how metaphors in the Australian press over the last 165 years which have generally constructed migration as a threat to the integrity of the nation, are repurposed to counter the claims embedded within them. For example, while invasion, swamping and flooding are generally recruited to negative ends, the same tropes are used to argue that fears of invasion are unjustified, that numbers of migrants are too small to swamp the nation and that the so-called floods of foreigners are overstated. However, this does not necessarily result in a decrease in metaphor use, nor challenge the fundamental implications of the metaphors. We explore how the repurposing occurs, and why it may not be an effective tool for anti-racist action.